Investigating the possibility of using second‐life batteries for grid applications. Issue 3 (27th May 2022) - Rahil, Abdulla; Partenie, Eduard; Bowkett, Mark; Nazir, Mian H.; Hussain, Muhammad M.
Abstract: This paper investigates the potential for use of batteries from retired plug‐in hybrid electric vehicles (PHEVs) in specific grid applications. In this study, project, a reference capacity test was performed to check the state of health, state of charge (SOC) and battery durability of a PHEV battery, and the pack was then tested under duty cycles for different grid applications to determine whether it would satisfy such applications in technical terms. The duty cycles considered are peak shaving, frequency regulation, photovoltaic (PV) smoothing and renewable energy firming. The data show that the battery can satisfactorily fulfil the requirements of peak shaving applications in terms of stability and battery retention capacity, and that the requirements of the frequency regulation service are also partially met. The untracked time for the battery signal was 4% (slightly exceeding the condition set for passing the tracking test, which is 2%). The SOC and temperature were within permitted limits. The battery, however, did not achieve good performance for PV smoothing or renewable energy (RE) firming. The untracked times were 14% and 11% for PV smoothing and RE firming, respectively (greatly exceeding the 2% condition for passing the tracking test). The SOC and temperature for the PV smoothing were within acceptable limits. The pack failed to complete the RE firming cycle as the SOC reached maximum safety limits after 6 h and 23 min, whereas the duty cycle is 10 h long. Abstract : Main stages of the second life battery use.